Long-term outcome after transcatheter mitral annuloplasty for secondary mitral regurgitation. (8th February 2021) - Lavall, D; Bruns, J; Stoebe, S; Hagendorff, A; Laufs, U
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: The long-term effects of transcatheter mitral valve annuloplasty (TMVA) for secondary mitral regurgitation is unknown. Purpose: We studied the clinical outcome and the effects on left ventricular (LV) function and remodeling and on mitral regurgitation (MR) severity after TMVA using the Carillon annuloplasty device. Methods: We analyzed 33 consecutive patients with symptomatic MR who were treated with TMVA at Leipzig University Hospital between 2012 and 2018. Echocardiography was performed before TMVA and at follow-up. MR severity was quantitatively assessed by regurgitant volume (calculated as LV total stroke volume – LV forward stroke volume) and regurgitant fraction (calculated as regurgitant volume / LV total stroke volume). Results: Mean age was 80 ± 10 years, 19 patients were women. A Society of Thoracic Surgeons (STS) score of 8.1 ± 7.2% indicated high risk status for mitral valve surgery. In 26 patients, mitral regurgitation resulted from LV remodeling and LV dysfunction, 7 suffered from left atrial dilatation. LV ejection fraction at baseline was 38% (30-49%; median, interquartile range). During a mean follow-up time of 45 ± 20 months, 17 patients died, 2 patients withdraw consent, and 4 patients were lost. Of the remaining patients, 4 were hospitalized for decompensated heart failure, and 2 underwent additional transcatheter edge-to-edge mitral valve repair. At follow-up, NYHA functional class improved from 95% in class III/IV at baseline to 70% in class I/II with no patients in NYHA class IV (p < 0.0001). Mitral regurgitant volume was reduced from 27mL (25-42mL) to 8mL (3-17mL) (p = 0.035) and regurgitant fraction from 43% (32-54%) to 11% (8-24%) (p = 0.020). LV end-diastolic volume index (92mL/m2 (71-107mL/m2) vs. 67mL/m2 (46-101mL/m2), p = 0.084) and end-systolic volumes index (51mL/m2 (44-69mL/m2) vs. 32mL/m2 (20-53mL/m2), p = 0.037) decreased. Thus, total stroke volume remained similar (38mL/m2 (33-43mL/m2) vs. 33mL/m2 (26-44mL/m2), p = 0.695) while LV ejection fraction increased (43% (31-49%) vs. 54% (46-57%), p = 0.032). Forward stroke volume, heart rate and forward cardiac output remained unchanged. Blood pressure was similar at baseline and at follow-up. Conclusion. Among high risk patients undergoing transcatheter mitral valve annuloplasty for symptomatic secondary MR, mortality was about 50% at 4 years. In the surviving patients, reduced MR severity was associated with fewer heart failure symptoms, reverse LV remodeling and improved LV function.